Tantangan Implementasi Nilai-Nilai Pancasila di SD Negeri 001 Bagan Batu Kota - Ayu Syofia Cindy; Supentri Supentri (Jurnal Nakula : Pusat Ilmu Pendidikan, Bahasa dan Ilmu Sosial, 2024)
The objective of this study is to identify the obstacles and examine the execution of Pancasila principles at SDN 001 Bagan Batu Kota. This study employs a qualitative research style that focuses on the interpretation, logic, specific definitions, and descriptions of the items under investigation. Methods of gathering data include observation, interviews, and documentation. Utilising data analysis techniques such as reduction, which involves the selection of significant data, and data presentation, which involves the consolidation of multiple data points into a single, relevant selection. Conclusion refers to the process of collecting evidence in order to reach a decision or judgement. The research findings indicated that SD Negeri 001 Bagan Batu Kota effectively implemented Pancasila values. Both teachers and the school incorporated Pancasila values into their teaching practices. However, they faced various challenges and obstacles, including the influence of external factors that introduced different cultural norms. The classroom atmosphere is adversely affected, and teachers and schools face the issue of raising student awareness, as pupils are resistant to guidance. The school encounters problems and impediments in its endeavour to offer instruction and instill positive habits.